(untitled) (Conference Zone, 2022)
Psoriasis is 5-10 % of all skin diseases. The symmetry of psoriasis rashes to a certain extent points to a disturbance in the activity of the central nervous system. Recently, there is some evidence that psoriasis is caused by a virus. However, it cannot be conclusively proven that psoriasis is viral in nature. No one has yet been seen to have contracted the disease from a patient with psoriasis. Many researchers consider psoriasis to be among genodermatoses.